The Association Between Fathers' Fatherhood Characteristics and High School Students’ General Health in Shiraz in 2015 - Shohreh Javadpour; Mehdi Kargar; Hajar Haghshenas; Mohammad Hossein Kaveh (Journal of Health Sciences and Surveillance System, 2019)
Introduction: The role of fathers in adolescents’ health is regarded as less important than mothers. This necessitates considering their role more than before. The present study was conducted to investigate the associations between high school students’ demographic profile and their general health with the fatherhood characteristics of their fathers. Methods: This descriptive-analytical and cross-sectional investigation was conducted among 604 girl and boy students in 2015 in Shiraz (Iran). The data collection tools included two self-administered questionnaires and a General Health Questionnaire (GHQ). Two self-administered questionnaires consisted of 5 demographic and 16 fatherhood characteristics questions. They were selected through a simple random sampling method, and the data were analyzed by Pearson correlation and descriptive statistics. The significance level was considered as 5%. Results: The findings showed that 495 students (46.90% girls and 53.10 boys) participated in the present study. They also demonstrated that 382 students were between 15-17 years old (79.20%) and 113 of them (20.80) aged about 18-19. There was significant associations between the mean scores of students general health and some of their fatherhood characteristics (P value=0.01). Some of their demographic information was also correlated to their general health significantly. The mean scores of fatherhood characteristics and students’ general health were, in turn, 38.56 (SD=14.6) and 44.99 (SD=9.69).  Conclusion: This study demonstrated the role of fathers in their offspring’s health status. It makes it necessary to educate fathers and reinforce their capabilities to promote their children’s health.